(3GdCfhGQ GdefHdLI aj HSW CSQGQ GdefaQLIs - (3CHh GdYHGS CMeO Hf CHi RjO YHO GdQMef GdfbGhSs; (3jhSa Hf eMeO Hf jhSa GdJhRQj , GdJdeSGfj, CHh GdaVd, GHf GdfMhqj,J (B513 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi JaQO HGdHbGA hGdbOe CeG HYO aEf Chdi eG Yfi HY GdYGbd NhjUI faSg hUdGM eG GNJd ef UaGJg s
(3BNQgG (B:s
(3CSCdc Cf dGJThg NdbfG HfGQLfge hgPG BNQ CfhGQ GdefHdLI ef CSQGQ GdefaQLI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B247 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B334s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs